Platelets 2020
DOI: 10.5772/intechopen.93181
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Platelets: Should I Stay or Should I Go?

Abstract: In this chapter, we discuss different topics always using the microRNA as the guiding thread of the review. MicroRNAs, member of small noncoding RNAs family, are an important element involved in gene expression. We cover different issues such as their importance in the differentiation and maturation of megakaryocytes (megakaryopoiesis), as well as the role in platelets formation (thrombopoiesis) focusing on the described relationship between miRNA and critical myeloid lineage transcription factors such as RUNX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 112 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…Since the largest pool of microvesicles is derived from platelets, a substantial ratio of cell-free miRNAs is transferred from activated platelets into other cell types and interfere with gene expression ( Águila et al, 2020 ). Based on former results, platelet-derived miR-223 regulated EFNA1 and FBXW7 gene expression at mRNA level in HUVECs ( Laffont et al, 2013 ), while others reported the inhibitory role of platelet miR-320b on endothelial ICAM-1 expression after myocardial infarction ( Gidlöf et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the largest pool of microvesicles is derived from platelets, a substantial ratio of cell-free miRNAs is transferred from activated platelets into other cell types and interfere with gene expression ( Águila et al, 2020 ). Based on former results, platelet-derived miR-223 regulated EFNA1 and FBXW7 gene expression at mRNA level in HUVECs ( Laffont et al, 2013 ), while others reported the inhibitory role of platelet miR-320b on endothelial ICAM-1 expression after myocardial infarction ( Gidlöf et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the largest pool of microvesicles is derived from platelets, a substantial ratio of cell-free miRNAs is transferred from activated platelets to other cell types and interfere with gene expression. 65 As these regulatory processes can be targeted by silencing RNA molecules as well as mimics, it is important to characterize the miRNA changes during sepsis so that these processes can be appropriately interfered. We have described in a series of septic patients by a TaqMan OpenArray technique that out of 390 platelet miRNAs, 121 were significantly decreased and 61 were upregulated in sepsis versus controls.…”
Section: A Potential Novel Pathway In Interfering With Sepsis Induced...mentioning
confidence: 99%